If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 12m + -2 = 6m + 30 + -2m Reorder the terms: 8 + -2 + 12m = 6m + 30 + -2m Combine like terms: 8 + -2 = 6 6 + 12m = 6m + 30 + -2m Reorder the terms: 6 + 12m = 30 + 6m + -2m Combine like terms: 6m + -2m = 4m 6 + 12m = 30 + 4m Solving 6 + 12m = 30 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 6 + 12m + -4m = 30 + 4m + -4m Combine like terms: 12m + -4m = 8m 6 + 8m = 30 + 4m + -4m Combine like terms: 4m + -4m = 0 6 + 8m = 30 + 0 6 + 8m = 30 Add '-6' to each side of the equation. 6 + -6 + 8m = 30 + -6 Combine like terms: 6 + -6 = 0 0 + 8m = 30 + -6 8m = 30 + -6 Combine like terms: 30 + -6 = 24 8m = 24 Divide each side by '8'. m = 3 Simplifying m = 3
| 14x^3=23x | | 0=-11+-10(0) | | x^2(x^2-9)-25(x^2-9)=0 | | 3w-19w=144 | | 3x+3x=12 | | (-15/7)p=-3 | | 5ln(7x)=10 | | 6y+12=3x | | 26y-31=y-(-33) | | -3=-10z+6 | | 2r+15r=119 | | 9x^4-19x^2+2=0 | | z/4=-22 | | x=-11+10(1) | | -3x^2+x+70=0 | | 8/-10=y | | 36v^2+60vg+25g^2=0 | | 8+1/6y=0 | | 7/8-1/5 | | 30x^3+39x^2-9x=0 | | 4-(3x-5)=-4(3x-2) | | 2u^2-8= | | B(x-a)=c | | 3(-2)=6 | | 3(s+22)=4(5+12) | | u^2+7u+10= | | 5+3=-10y | | 5x-2y=183 | | -(3y+3)-(-2y-6)=-2 | | 4m=-66 | | -2(2b+2)+(9b-3)=0 | | 7(2x-5)-3x=4+(8x+1) |